Paket Edukasi Ibu Hamil untuk Mewujudkan Anak Sehat dan Cerdas Melalui Pendekatan Asuhan Kebidanan Holistik - Khuzaiyah, Siti; Kristiyanti, Rini (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2020)
Children are an investment in a nation, which must be made to optimize their physical and spiritual health. Optimization of children’s health must be done holistically since the child is in the womb. This community service was carried out to increase the knowledge, motivation, and skills of pregnant women in realizing healthy and smart mothers and children. The method of this activity was carried out with the stages of education, empowerment, and mentoring. The target of this activity was pregnant women. The form of the activities was community-based in collaboration with the village government of Pangkah Village, Karangdadap Sub-district, Pekalongan District, and Puskesmas (Public health center) Karangdadap. The education for pregnant women was given once a month, including spiritual hypnotherapy relaxation, stimulating the baby’s intelligence, and exclusive breastfeeding. This activity was attended by 21 pregnant women and lasted for five months. The results obtained are 1) 17 people (81%) have good knowledge of brain booster, relaxation, and proper breastfeeding, and 19 people (91%) have a strong motivation in applying the three skills; 2) Mothers can do spiritual relaxation hypnotherapy during pregnancy, and; 3) Mothers can practice stimulating their baby’s intelligence from the womb with the brain booster method.